Study of material characterization of samarium doped ceria-rice husk ash silica (SDC-RHASiO2) - Jaidi, Zolhafizi; Azmi, Mohd Azham; Mokhtar, Muhammad Akmal; Abd Rahman, Hamimah; Mahzan, Shahruddin; Ismail, Azzura (2024)
Additional of metal oxide such as copper oxide, lithium oxide and iron oxide into ceria-based electrolyte had been commercialized to improve the performance of the ceria based material in microstructure modification. In this study, the effect of samarium doped ceria with the addition of rice husk ash silica on its characterization is described. Samarium doped ceria (SDC) with addition of 1.0 wt.% of rice husk ash silica (RHASiO2) was prepared by ball milling method. The SDC-RHASiO2 composite pellets were produced by uniaxial press and were sintered at 700°C. Material characterizations of SDC-RHASiO2 sample were identifying by X-ray diffraction (XRD) for crystalline structures, porosity test and scanning electron microscope (SEM) for surface morphology and microstructures. Based on XRD result obtained, it has been found that the result for SDC-RHASiO2 powder only showed the face-centered cubic lattice structure of (Sm.20Ce.80O1.90) without additional impurity phases. SEM micrographs indicated that the porosity percentage decreases when the RHASiO2 was added into SDC. This mixed material is believed could improve the structure as well as the performance of undoped SDC